Identifying the Components of Social Capital by Categorical Principal Component Analysis (CATPCA) - Saukani, Nasir; Ismail, Noor Azina (Kluwer (now part of Springer), 2019)
Social capital is a promising concept, widely used by social science researchers in analysing factors that contribute to the persistence of various economic issues. Unfortunately, the search for the best way to define, measure and classify the appropriate components that constitute this intangible form of capital is far from complete. Generally, data on social capital are qualitative in nature (mostly of the nominal and ordinal types) and encompass a large number of variables. This challenges the researcher to find the best way to reduce these data to a small number of composites to be used as a proxy of measurement in further analysis. Although principal component analysis (PCA) is considered an appropriate method and has been widely adopted in past studies, the requirement that data must be at the numeric measurement level, as well as the assumptions of linear relationships between variables, might hinder the use of PCA in working with social capital data. Categorical principal component analysis (CATPCA) is a more flexible alternative, suitable for variables of mixed measurement levels (nominal, ordinal, and numeric) that may not be linearly related to each other. Based on theory and past studies, questionnaires have been constructed and fieldwork has been carried out to gather data on social capital in Malaysia. Later, using CATPCA, 42 potential variables were identified to represent components of social capital. Final results indicate that after withdrawing 9 variables with bad fits, CATPCA has categorized the balance of 33 variables into four dimensions of social capital. These dimensions can be described by 5 principal components, which have been identified as influence of spirituality and culture, benefits from interaction with friend, trusted person during financial difficulties, benefits from financial aid receive and benefits from involvement in association. The first component represents culture/spirituality, the new dimension created by this study to address social capital from the perspective of a developing country. The second, third, fourth and fifth components are in line with the consensus reached by scholars and advocates regarding the elements or components of social capital. The second and fifth actually fall under the rubrics of the social relation/networks dimension while the third and fourth under trust and norms. © 2018, Springer Science+Business Media B.V., part of Springer Nature.